Lysozyme-loaded lipid-polymer hybrid nanoparticles: preparation, characterization and colloidal stability evaluation. (1st November 2016) - Devrim, Burcu; Kara, Aslı; Vural, İmran and Bozkır, Asuman
Abstract: Context: Lipid-polymer hybrid nanoparticles (LPNPs) are polymeric nanoparticles enveloped by lipid layers, which have emerged as a potent therapeutic nanocarrier alternative to liposomes and polymeric nanoparticles. Objective: The aim of this work was to develop, characterize and evaluate LPNPs to deliver a model protein, lysozyme. Materials and methods: Lysozyme-loaded LPNPs were prepared by using the modified w/o/w double-emulsion-solvent-evaporation method. Poly-ɛ-caprolactone (PCL) was used as polymeric core material and tripalmitin:lechitin mixture was used to form a lipid shell around the LPNPs. LPNPs were evaluated for particle size distribution, zeta potential, morphology, encapsulation efficiency, in vitro drug release, stability and cytotoxicity. Results: The DLS measurement results showed that the particle size of LPNPs ranged from 58.04 ± 1.95 nm to 2009.00 ± 0.52 nm. The AFM and TEM images of LPNPs demonstrate that LPNPs are spherical in shape. The protein-loading capacity of LPNPs ranged from 5.81% to 60.32%, depending on the formulation parameters. LPNPs displayed a biphasic drug release pattern with a burst release within 1 h, followed by sustained release afterward. Colloidal stability results of LPNPs in different media showed that particle size and zeta potential values of particles did not change significantly in all media except of FBS 100% for 120 h. Finally, the results of a cellular uptake study showed that LPNPs were significantly taken up by 83.3% in L929 cells. Conclusion: We concluded that the LPNPs prepared with PCL as polymeric core material and tripalmitin:lechitin mixture as lipid shell should be a promising choice for protein delivery.